Alumnus User Satisfaction of Fakultas Keguruan Dan Ilmu Pendidikan Universitas Sebelas Maret - Murwaningsih, Tri (Proceeding of International Conference on Teacher Training and Education, 2016)
Educational management is the management of educational resources in accordance with management functions to achieve educational goals effectively and efficiently. Educational resource consists of men, money, materials, methods, machine, market, minute, and information. Management functions such as planning, organizing, actuating, and controlling are performed sequentially. Controlling function is to monitor and evaluate the results of actuating function in comparison with the goals to be achieved. One effort in the controlling of FKIP UNS is the alumnus user satisfaction survey. Information survey results are used for policy-making considerations in the improvement and development of quality improvement of students so that alumnus users obtain qualified labor. Informations are obtained from the 39 agencies both formal educational institutions (primary schools, junior high schools, senior high schools, and vocational schools) or non-formal educational institutions in 2012. The research instrument is a questionnaire to determine the ten alumnus abilities. From the questionnaires showed that alumnus FKIP UNS including in the category of very capable in leadership skills, science, the use of information technology, active in school organization. Alumnus FKIP UNS including in the category of capable in communication skills, teamwork, motivation and self-development, integrity, and entrepreneurship. Alumnus FKIP UNS including in the category of less capable in mastery of the English.